Effects of Dietary Barley Starch Contents on the Performance, Nutrient Digestion, Rumen Fermentation, and Bacterial Community of Fattening Hu Sheep - Ma, Xiaowen; Zhou, Wenjing; Guo, Tongqing; Li, Fei; Li, Fadi; Ran, Tao; Zhang, Zhian; Guo, Long (Frontiers in Nutrition, 2022)
The objective of this experiment was to investigate the effects of substituting corn starch (CS) with barley starch (BS) on the growth performance, nutrient digestion, rumen fermentation, and bacterial community of fattening Hu sheep. Seventy-two Hu lambs with similar initial body weight (BW, 29.70 ± 1.70 kg) were randomly assigned to four treatments, with 18 lambs per group. The four experimental diets have identical starch contents but with different starch sources as 100% starch from corn (BS-0), 33% starch from barley and 67% starch from corn (BS-33), 67% starch form barley and 33% starch from corn (BS-67), and 100% starch from barley (BS-100). All lambs were reared in individual units and fed high-concentrate diets (85% concentrate in diets based on DM). The experimental period included 7 days for adaptation and 63 days for data collection. Sixteen ruminal cannulated Hu sheep were divided into 4 groups and received the four experimental diets to determine the dynamics of ruminal pH. The average daily gain (ADG), and BW gain of lambs linearly decreased (P < 0.05), whereas the F/G linearly increased (P < 0.05) with increasing dietary proportions of BS. Digestibility of DM, OM, NDF, ADF, starch, and gross energy (GE) decreased (P < 0.05) with increasing dietary BS contents. Ruminal mean pH decreased (P < 0.05) with increasing proportions of dietary BS, accompanied with linearly increased (P < 0.05) time and area of ruminal pH below 5.80 or 5.60. Increasing dietary proportions of BS linearly decreased (P < 0.05) the molar proportion of acetate, but linearly increased (P < 0.05) the molar proportion of propionate. Sheep of the BS-0 and BS-33 treatments had a less (P < 0.05) relative abundance of Selenomonas ruminantium than that of sheep of the BS-67 treatment, but a greater (P < 0.05) relative abundance of Ruminococcus albus than that of sheep of BS-100 treatment (P < 0.05). In conclusion, feeding a high-concentrate corn-based diet for fattening Hu sheep improved performance and rumen fermentation parameters when compared to a barley-based diet.